Dari Istana Babel ke Indonesia Masa Kini: Relevansi Spiritualitas Daniel bagi Penguatan Toleransi Dalam Moderasi Beragama - Anugerah Joyser; Yehuda Indra Gunawan (Vox Dei: Jurnal Teologi dan Pastoral, 2025)
Indonesia's religious diversity is both a national treasure and a potential source of religious conflict if the government lacks a robust mechanism to regulate interfaith coexistence. In recent years, the government has attempted to foster tolerance and moderation among religious communities, but in reality, cases of interfaith intolerance remain frequent. These incidents of intolerance not only result in financial losses but also psychological trauma and a sense of insecurity in religious practice and worship. This fact indicates that tolerance in religious moderation and the implementation of the first principle of Pancasila, "Belief in the One and Only God," have not been optimally implemented. This research was conducted as an effort to strengthen tolerance in religious moderation in Indonesia through the application of Daniel's spirituality. A person's spiritual life in God will build a strong faith and tolerance towards fellow religious people by rejecting all forms of violence in the name of religion. Daniel's success as a moderate and tolerant figure in Babel can be a reference for the life of tolerance between religious communities in Indonesia. This study uses a qualitative research method with an interpretive-theological literature study approach, where the researcher interprets the book of Daniel and studies various writings in books and previous research. The results of this study show that Daniel's spirituality is very relevant to strengthening tolerance in religious moderation, namely by building a commitment to the value of truth without fanaticism, respecting and supporting the government and applicable state laws, and spiritual integrity that brings tolerance and social justice.